ZrN and ta-C coatings on titanium for biomedical applications: Improved adhesion, corrosion, antibacterial activity, and cytotoxicity properties - Aslan, Naim; Aksakal, Bunyamin; Cihangir, Salih; Cetin, Fadime; Yilmazer, Yasemin (Springer Heidelberg, 2023)
Commercially pure titanium (CP-Ti) is extensively used in biomedical applications. However, numerous qualities, including mechanical strength, corrosion resistance, and wear resistance, must be established for long-term performance as an implant material. This study investigates the enhancement of surface properties of CP-Ti through physical vapor deposition (PVD) with ZrN and ta-C (tetrahedral amorphous carbon). Among the coatings, ZrN revealed best overall results, such as adhesion, corrosion, microhardness, and wettability, excluding cell viability when compared to ta-C. E. coli and S. aureus were employed for antibacterial activity and MTS cell viability experiments. Compared to a-titanium, hardness tests revealed 91% increase in ZrN coating, and %22 increase in ta-C coating. Super-hydrophobicity and excellent antibacterial activity were found for ZrN coatings in comparison to ta-C. These findings emphasize the potential of ZrN and ta-C coatings to improve the surface properties of titanium, encouraging it to be used in biomedical devices.
Keywords: & alpha;-Titanium; PVD; Corrosion; Antibacterial activity; Cell viability